Arterial pre-hypertension and hypertension in intracranial versus extracranial cerebrovascular stenosis - Wang, Dandan; Jonas, Jost B. (European journal of neurology, 2015)
Background and purpose: Since it has remained unclear whether arterial pre-hypertension is a risk factor for cerebrovascular diseases, potential associations between arterial pre-hypertension and intracranial arterial stenosis (ICAS) and extracranial arterial stenosis (ECAS) were assessed. Methods: The population-based Asymptomatic Polyvascular Abnormalities in Community Study was a sub-study of employees and retirees of the coal mining industry in China. Our study examined asymptomatic polyvascular abnormalities in a general population and with an age of 40+ years without history of stroke, transient ischaemic attacks and coronary heart disease. ICAS was diagnosed by transcranial Doppler sonography and was defined by peak flow velocity criteria; ECAS was diagnosed by carotid duplex sonography and was defined by the diameter of the common carotid artery or internal carotid artery. Results: Out of 4422 study participants, 711 (16.1%) subjects showed an asymptomatic ICAS and 292 (6.6%) showed an asymptomatic ECAS. After adjusting for relevant risk factors, higher prevalence of ICAS was significantly associated with higher prevalence of pre-hypertension [odds ratio (OR) 1.55; 95% confidence interval (CI) 1.11, 2.16; P = 0.010] and hypertension (OR 1.80; 95% CI 1.53, 2.11; P < 0.001). Stratified by gender, the association was stronger for men than for women. Asymptomatic ECAS was not significantly associated with the prevalence of pre-hypertension (OR 0.78; 95% CI 0.55, 1.10) or of hypertension (OR 1.06; 95% CI 0.91, 1.24). Conclusions: The results suggest that arterial pre-hypertension in addition to hypertension is associated with a higher prevalence of asymptomatic ICAS, more in men.